Regulation of Road Accident Externalities when Insurance Companies have Market Power - Maria Dementyeva; Paul R. Koster; Erik T. Verhoef (Tinbergen Institute, 2013)
Accident externalities are among the most important external costs of road transport. We study the regulation of these when insurance companies have market power. Using analytical models, we compare a public-welfare maximizing monopoly with a private profit-maximizing monopoly, and markets where two or more firms compete. A central mechanism in the analysis is the accident externality that individual drivers impose on one another via their presence on the road. Insurance companies will internalize some of these externalities, depending on their degree of market power. We derive optimal insurance premiums, and manipulable taxes that take into account the response of the firm to the tax rule applied by the government. Furthermore, we study the taxation of road users under different assumptions on the market structure. We illustrate our analytical results with numerical examples, in order to better understand the determinants of the relative performance of different market structures.
Keywords: D43; D62; R41; R48; 330; accident externalities; traffic regulation; safety; second-best; market power